The problems of the southward enlargement of the EC - Konrad Neundörfer (Intereconomics, 1983)
The process of southward enlargement of the European Community is now well under way; Greece has been a full member since 1st January 1981 and intensive negotiations with Spain and Portugal are proceeding, although a successful conclusion is not yet in sight. Our article discusses the political and economic implications of enlargement for both the acceding countries and the existing community, concluding with a number of proposals regarding the course to be followed in future.
Keywords: 330; European Community